If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + 3(s + -6t) = 0 8 + (s * 3 + -6t * 3) = 0 8 + (3s + -18t) = 0 Solving 8 + 3s + -18t = 0 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + 3s + -8 + -18t = 0 + -8 Reorder the terms: 8 + -8 + 3s + -18t = 0 + -8 Combine like terms: 8 + -8 = 0 0 + 3s + -18t = 0 + -8 3s + -18t = 0 + -8 Combine like terms: 0 + -8 = -8 3s + -18t = -8 Add '18t' to each side of the equation. 3s + -18t + 18t = -8 + 18t Combine like terms: -18t + 18t = 0 3s + 0 = -8 + 18t 3s = -8 + 18t Divide each side by '3'. s = -2.666666667 + 6t Simplifying s = -2.666666667 + 6t
| x^2y^4z/(x^2y)3*(x^10y^5z^4)^2/y^3z^2 | | 3(8+3/2y)+4y=7 | | 1/2(n+5)+1/3(n+3)=6 | | 5+2(x-3y)= | | -75=5(7n+6) | | 7t+18-4= | | -1x^2+12x-36=0 | | 2x^4-2x^3-11x^2+4x+8=0 | | 4(3x+7)-6(3x-5)=10x+3(2x-8) | | 4.9x^2+8x-30=0 | | .5(2m+6)=.25(8+8m) | | 3x^2-8x=9 | | 4.9x^2+8t-30=0 | | .25(2m-20)=.25(8-8m) | | (3x+7)(5x-1)= | | -35=5-2x+7x | | (2lb-5)-5(4b+4)=-3 | | 10-24d=4-5(2d+9)+3d | | 35-15x=-8x | | 7k+1=2k-1 | | 8w+w+6w= | | 35-15x=8x | | .5(-12m+6)=.25(-20+8m) | | (-8x-7)(-7x-3)= | | N+19=16 | | 6x^2+78x=-216 | | (8x+6)(8x^2+7x+8)= | | 8c*3e= | | -p-2p+3=-6 | | 6+x+-5+2x=x | | 29=2u+13 | | X-3=7-4x |